Self-passivation hole transport material and preparation method and application thereof
By designing a self-passivating hole transport material with a macrocyclic structure containing glucopyranose units, the problems of complex synthesis, high cost and additive dependence in the prior art are solved, and the efficient photoelectric conversion and interface carrier transmission of perovskite solar cells are realized.
Patent Information
- Application Number
- CN202411762560.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-14
AI Technical Summary
The synthesis steps of spiro-OMeTAD, used in existing perovskite solar cells, are complex, costly, and require additional additives to enhance passivation, but this increases manufacturing costs and reduces the environmental stability of the device.
A self-passivation hole transport material is designed, which contains a macrocyclic structure of glucopyranose-like glucopyrane units or glucopyrane-like units. By introducing active hydroxyl groups and R1, R2, and R3 groups with hole transport capabilities, self-passivation of perovskite layer defects is achieved, and the interaction between perovskite and hole transport layer is promoted through strong hydrogen bonding.
The synthesis steps are simplified, cost is reduced, dependence on additional additives is reduced, photoelectric conversion efficiency of perovskite solar cells is improved, and interfacial carrier transmission is promoted.
Smart Images

Figure CN119613587A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of photoelectric materials and solar cell materials, and in particular to a self-passivating hole transport material and a preparation method and application thereof. Background Art
[0002] Solar cells, as a method of generating clean energy, are one of the important means to achieve carbon peak and carbon neutrality in the future; perovskite solar cells (PSCs) are a high-performance, simple-to-prepare new type of solar cells. Since their appearance, their photoelectric conversion efficiency has exceeded 26%. It is a solar cell with great potential. As an indispensable part of perovskite solar cell devices, hole transport materials play an important role in optimizing the interface transport and passivation defects of the interface layer. At present, the most commonly used organic small molecule hole transport material is 2,2,7,7-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9-spirobifluorene (spiro-OMeTAD). Due to its many synthesis steps and complex process, it leads to high synthesis cost, which is not conducive to large-scale application. In addition, when using spiro-OMeTAD as a hole transport material for perovskite solar cells, additives need to be added to increase its passivation function. However, the addition of additives not only increases the manufacturing cost but also reduces the environmental stability of the device. Therefore, it is of great significance to develop a hole transport material with a simple synthesis process and self-passivation function. Summary of the invention
[0003] One of the purposes of the present invention is to provide a self-passivating hole transport material. The self-passivating hole transport material prepared by the method is applied to perovskite solar cells. As a hole transport layer, it can enhance the interaction with the perovskite layer, realize the self-passivation of the hole transport material on the perovskite defects, reduce the addition of additives, and at the same time, the strong interaction between the hole transport layer and the perovskite layer can also promote the carrier transport between the perovskite layer and the hole transport layer, and improve the charge extraction capability.
[0004] To achieve the above object, the present invention adopts the following technical solution: a self-passivating hole transport material having the general structural formula of the following formula (1):
[0005]
[0006] Wherein, n in formula (1) represents the number of pyranose glucose units or pyranose glucose-like units, which is any integer from 5 to 20, and the pyranose glucose units or pyranose glucose-like units form a macrocyclic structure connected end to end; the organic groups R1, R2, and R3 are the same or different, and are independently selected from one of hydrogen, halogen, alkane, alkene, alkynyl, aromatic, thienyl, pyrrolyl, and pyridyl.
[0007] Further improvements as self-passivating hole transport materials:
[0008] Preferably, R1, R2, and R3 can also be independently selected from at least one of the substituents of formula (2):
[0009]
[0010] In formula (2), R4 and R5 can be independently selected from a benzene ring, a thiophene ring, a pyrrole ring, or a pyridine ring; R6 is a triphenylamine substituent, a C1-C6 alkyl substituted triphenylamine, a C1-C6 alkoxy substituted triphenylamine, a diphenylamine, a C1-C6 alkyl substituted anilino, or a C1-C6 alkoxy substituted diphenylamine; R1, R2, R3, R4, R5, and R6 groups are the same or different; m represents the number of substituents R4, which is any integer from 1 to 6.
[0011] Preferably, the pyranose glucose units or pyranose-like units form a macrocyclic structure connected end to end and have the general characteristics of formula (3):
[0012]
[0013] Wherein k represents the number of pyranose glucose units or pyranose glucose-like units in the macrocyclic structure of the general formula required by formula (3), and the value is any integer between 0 and 15.
[0014] The second object of the present invention is to provide a method for preparing the self-passivating hole transport material described in any one of the above, comprising the following steps:
[0015] S1. A compound having a macrocyclic structure composed of pyranose glucose units or quasi-pyranose glucose units is used as a raw material, 1-toluenesulfonyl-1H-imidazole or p-toluenesulfonyl chloride is used as a reactant, and the raw material and the reactant are added to an acidic or alkaline solvent in a molar ratio of 1:(1-50) to obtain a mixed solution;
[0016] S2, reacting the mixed solution under inert gas protection, first in an ice bath and then in heating or directly in heating, washing with acid, distilling and filtering to obtain a solid, subjecting the solid to reverse phase column chromatography, eluting with a mixed solvent, concentrating and drying to obtain an intermediate;
[0017] S3, mixing the intermediate and a substituent containing three substituents of R1, R2 and R3 in a molar ratio of 1:(1-50), and adding the mixture into a solvent to obtain a mixed reaction liquid; the substituent containing three substituents of R1, R2 and R3 is a trifluoromethylsulfonic acid substituent containing three substituents of R1, R2 and R3, or a yellow acyl chloride substituent containing three substituents of R1, R2 and R3, or an amino substituent containing three substituents of R1, R2 and R3;
[0018] S4. The mixed reaction liquid is reacted at a temperature of 50-180°C for 6h-72h, the product is added to acetone, filtered to obtain a solid, the solid is dried and then subjected to reverse phase column chromatography, eluted with a mixed solvent, and dried to obtain a solid, the solid is washed with acetone and then vacuum dried to obtain a self-passivating hole transport material.
[0019] Further improvement of the preparation method as self-passivating hole transport material:
[0020] Preferably, the compound containing a macrocyclic structure composed of pyranose glucose units or pyranose glucose-like units is an organic molecule having the general structure of formula (4), wherein h in formula (4) is any integer between 0 and 15;
[0021]
[0022] Preferably, the acidic or alkaline solvent in step S1 is a pyridine solvent, or a mixed solvent of dioxane, water and carbonate buffer solution in a volume ratio of 1:1:1.
[0023] Preferably, the mixed solvent in step S2 and step S4 is a methanol / water mixed solvent with a volume ratio of 1:1, or a methanol / water / dichloromethane mixed solvent with a volume ratio of 1:1:1.
[0024] Preferably, a phase transfer catalyst is further added to the mixed reaction liquid of step S3, and the phase transfer catalyst is one or a combination of two or more of crown ethers, alkyl-substituted amino hexafluorophosphates, alkyl-substituted ammonium bromides, 18-crown-6, and potassium carbonate.
[0025] Preferably, in step S2, the reaction time under ice bath conditions is 2 to 18 hours; and the reaction temperature under heating conditions is 50° C. to 180° C. and the reaction time is 2 to 8 hours.
[0026] The third object of the present invention is to provide an application of the above-mentioned self-passivating hole transport material in a photoelectric device, wherein the photoelectric device is a perovskite solar cell, comprising a transparent conductive substrate, an electron transport layer, a perovskite layer, a hole transport layer and a metal electrode, and the material of the hole transport layer is any one of the above-mentioned self-passivating hole transport materials.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The present invention aims at the problems that the traditional spiro-OMeTAD hole transport material has many synthesis steps, complex process, high synthesis cost, etc., designs and prepares a hole transport material with a passivation effect containing a macrocyclic structure composed of pyranose glucose units or pyranose glucose-like units, utilizes the relatively active hydroxyl groups in the macrocyclic structure composed of pyranose glucose units or pyranose glucose-like units, introduces R1, R2, R3 groups with hole transport ability, and simultaneously utilizes the strong hydrogen bonding effect of the hydroxyl groups in the macrocyclic structure composed of pyranose glucose units or pyranose glucose-like units, realizes the chelation of metal ions in perovskite, suppresses the defects of perovskite layer, increases the interaction between perovskite layer and hole transport material, and promotes interface carrier transmission. The present invention has few synthesis steps, simple process, and does not require the addition of additional additives and can obtain a higher photoelectric conversion efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to further illustrate the technical solution implemented by the present invention, the following is an illustration of the implementation method of the present invention in the form of an embodiment.
[0030] Figure 1 This is a molecular structure diagram of product 1 in Example 1 of the present invention.
[0031] Figure 2 This is a molecular structure diagram of product 2 in Example 2 of the present invention.
[0032] Figure 3 JV curves of perovskite solar cell devices prepared with product 1 in Example 1 of the present invention, product 2 in Example 2, and Spiro-OMeTAD in Comparative Example 1 as hole transport materials. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Based on the embodiments of the present invention, all other embodiments prepared by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.
[0034] The present invention is described in more detail and comprehensively below in conjunction with specific embodiments. It should be particularly noted that the specific embodiment described below is only one embodiment of the present invention and should not be construed as limiting the scope of protection of the present invention. The present invention is not limited to the contents described in this embodiment. Non-essential changes made by those skilled in the art according to the present invention still fall within the scope of protection of the present invention.
[0035] Unless otherwise specified, the terms used herein have the same general meanings as those understood by those skilled in the art. The terms used in the present invention are only for the convenience of describing specific embodiments of the present invention and are not limited to the present invention.
[0036] The "embodiments" mentioned in the present invention describe that the features, structures and other characteristics of the embodiments can be included in at least one embodiment of the present invention. The embodiments described in the present invention are not necessarily the same, and do not specifically refer to a certain molecular structure, feature, etc. The embodiments described in the present invention can be combined with other embodiments included in the present invention. The embodiments described in the present invention are one or more embodiments included in the present invention, and are not limited to specific embodiments. The embodiments of the present invention understood by those skilled in the art still belong to the scope of protection of the present invention.
[0037] Alkyl refers to a saturated substituent of primary, secondary or tertiary carbon with C1-C6 number, C1-C6 refers to a saturated substituent containing 1-6 carbon atoms; olefin refers to an olefin substituent with C1-C6 number and at least one carbon-carbon double bond; alkynyl refers to an alkynyl substituent with C1-C6 number and at least one carbon-carbon triple bond; aromatic refers to a substituent containing a benzene ring, wherein the benzene ring may carry a C1-C3 alkane substituent or a C1-C3 alkoxy substituent; C1-C3 refers to a saturated alkane substituent containing 1-3 carbon atoms; alkoxy substituent refers to a saturated substituent containing different numbers of carbon atoms with an oxygen atom at the end; thienyl refers to a thiophene substituent containing a C1-C6 saturated substituent; pyrrolyl refers to a pyrrole substituent with a C1-C6 saturated substituent; pyridyl refers to a pyridine substituent containing a C1-C6 saturated substituent;
[0038] The biaryl group refers to a condensed aromatic hydrocarbon substituent containing 1 to 3 benzene ring structures.
[0039] Halogen refers to F, Cl, Br, I;
[0040] The present invention first describes a hole transport material having the structure described in formula (1) and formula (3). In some embodiments, R1, R2, and R3 may be the same or different; preferably, R1, R2, and R3 may be independently selected from hydrogen, chlorine, bromine, C1-C6 alkyl, C1-C6 alkoxy, C6-C14 aromatic or biaryl, thienyl, C1-C6 alkyl substituted thienyl, C1-C6 alkoxy substituted thienyl, C1-C6 alkyl substituted pyrrolyl, C1-C6 alkoxy substituted pyrrolyl, and pyridyl.
[0041] In some embodiments, R1, R2, and R3 can also be independently selected from at least one substituent having formula (2):
[0042]
[0043] The R4 and R5 can be independently selected from a benzene ring, a thiophene ring, a pyrrole ring, or a pyridine ring; R6 is a triphenylamine substituent, a C1-C6 alkyl substituted triphenylamine group, a C1-C6 alkoxy substituted triphenylamine group, a diphenylamine group, a C1-C6 alkyl substituted anilino group, or a C1-C6 alkoxy substituted diphenylamine group;
[0044] R1, R2, R3, R4, R5, and R6 groups are the same or different; m represents the number of substituents R4, which is any integer from 1 to 6.
[0045] Example 1
[0046] This embodiment provides a method for preparing a self-passivating hole transport material, and the specific preparation steps are as follows:
[0047] S1, a compound having a macrocyclic structure consisting of 6 pyranose glucose units as raw material 1 (as shown in the following formula (5)), 972 mg (1 molar equivalent) of raw material 1, 200 mg (1.05 molar equivalent) of p-toluenesulfonyl chloride as a reactant, and 50 ml of pyridine were added into a 100 ml flask to obtain a mixed solution;
[0048] S2. The mixed solution was reacted for 2 h under the protection of nitrogen inert gas and ice bath conditions, and then continued to react at 75°C for 2 h. After the reaction was completed, 5 ml of dilute hydrochloric acid was added for washing, and the volume was distilled under reduced pressure to about 5 ml, and then 300 ml of acetone was added for filtration to obtain a solid; the solid was subjected to reverse phase column chromatography, eluted with a methanol / water mixed solvent with a volume ratio of 1:1, and concentrated and dried to obtain 0.38 g (yield 33%) of a solid, which was recorded as intermediate 1. The mass spectrum [M+Na] + 1149.320;
[0049] S3, 100 mg of intermediate 1 (1 molar equivalent) and 111 mg of compound 4-(5-(4-(diphenylamino)phenyl)thiophen-2-yl)phenol (3 molar equivalents) were mixed, added to 50 ml of N,N-dimethylformamide, and 0.5 g of potassium carbonate solid and a small amount of 18-crown-6 (5% molar equivalent) solid were added as a phase transfer catalyst to obtain a mixed reaction liquid;
[0050] S4. The mixed reaction liquid was reacted at 100° C. for 8 h, the product was introduced into 300 ml of acetone, filtered to obtain a solid, dried and chromatographed using a reverse phase column with methanol / water / dichloromethane in a volume ratio of 1:1:1 as an eluent to obtain a solid. The solid was washed with acetone and dried in vacuo at 100° C. to obtain product 1 (42.6 mg, 33% yield), the structural formula of which is shown in the following formula (6); mass spectral data [M+Na-2H]: 1394.421; 1H NMR spectrum: 7.81 (d, 2H, J=8.0 Hz)7.32(d,2H,J=8.1Hz)7.30(s,1H),7.28(s,1H),7.26(m,2H)7.24(m,4H),7.05(d,2H,J=8.0Hz),6.98(m, 6H),5.1(m,6H),4.2(m,1H),4.05(m,2H),3.95(m,10H),3.80(m,6H),3.69(m,6H),3.61(m,6H),3.31(m,5H);
[0051]
[0052]
[0053] This embodiment also provides a method for preparing a perovskite solar cell, and the specific steps are as follows:
[0054] S1. The FTO conductive glass substrate was ultrasonically cleaned for 15 minutes using a cleaning agent, deionized water, acetone and isopropanol in sequence, the FTO substrate was blown dry using compressed air, and then the substrate was treated with ultraviolet ozone for 15 minutes to obtain a pretreated FTO substrate.
[0055] S2, preparation of tin oxide electron transport layer, add 1g of 15% tin oxide aqueous solution to 6ml deionized water, stir at room temperature for several minutes, obtain 2.14% tin oxide colloidal aqueous solution, and spin coat the solution on the pretreated FTO substrate surface by spin coating. The spin coating process is: spread 60μl solution on the FTO surface, spin coat at 3000 rpm for 30 seconds, anneal at 150 degrees for 30 minutes, and obtain the tin oxide electron transport layer.
[0056] S3, DMF and DMSO were mixed in a volume ratio of 4:1 to obtain a mixed solvent, and methylammonium chloride MACl and Cs 0.05 (FA 0.98 MA 0.02 ) 0.95 Pb(I 0.98 Br 0.02 )3 materials are added to the mixed solvent and dissolved, Cs 0.05 (FA 0.98MA 0.02 ) 0.95 Pb(I 0.98 Br 0.02 )3 concentration is 1.3M, MACl addition amount is 0.195M, and it is placed at 60°C for heating and stirring for 2 hours, and the perovskite precursor solution is obtained after it is completely dissolved; 40 μL of the perovskite precursor solution is added dropwise to the surface of the tin oxide electron transport layer, and the tin oxide electron transport layer is spin-coated at a speed of 4000 rpm for 30 seconds. 10 seconds before the end of the spin coating, 110 μL of anti-solvent chlorobenzene is added dropwise to the surface of the substrate to promote the rapid volatilization of the solvent, and then annealed at 120°C for 30 minutes, and cooled to room temperature to obtain a perovskite light-absorbing layer with a thickness of about 500 nm;
[0057] S4, dropping 40 μL of a 20 mg / ml chlorobenzene solution of the product 1 obtained in the present invention onto the perovskite layer, and spin coating at a speed of 3000 rpm for 30 seconds to obtain a hole transport layer with a thickness of 20 nm;
[0058] S5, the surface of the conductive substrate prepared in the above step is covered with a mask plate, and then placed in a thermal evaporation chamber, and evacuated to 10 -4 Pa below A Ag film with a thickness of 100 nm is deposited at a deposition rate as a metal counter electrode layer, thereby obtaining a perovskite solar cell using a self-passivating hole transport material.
[0059] Example 2
[0060] This embodiment provides a method for preparing a self-passivating hole transport material, and the specific preparation steps are as follows:
[0061] S1. Take a raw material containing 6 pyranose glucose units (as shown in formula (7)) as raw material 2, take a 100 ml flask, add 972 mg (1 molar equivalent) of raw material 2, 444 mg (2 molar equivalents) of 1-tosyl-1H-imidazole, 30 ml of a mixed solvent of 1,4-dioxane / water (1:1 volume ratio) and 15 ml of a carbonate buffer solution (PH=9.9) as a mixed solvent, and obtain a mixed solution;
[0062] S2. The mixed solution was reacted at 50°C for 2h under nitrogen inert gas protection, then 5ml of dilute hydrochloric acid was added for washing, the volume was concentrated to about 5ml, and then 150ml of acetone was added and filtered to obtain a solid; the solid was eluted on a reverse phase column with a methanol / water mixed solvent having a volume ratio of 1:1, and dried to obtain 0.52g (yield 45%) of solid intermediate 2 (as shown in formula (8)); the mass spectrum resolution was: [M+Na] + 1149.312.
[0063] S3, after mixing 100 mg of intermediate 2 (1 molar equivalent) and 111 mg (3 molar equivalents) of 4-(5-(4-(diphenylamino)phenyl)thiophen-2-yl)phenol compound, 50 ml of N,N-dimethylformamide was added, and 0.5 g of potassium carbonate solid and a small amount of 18-crown-6 (5% molar equivalent) solid were added as a phase transfer catalyst to obtain a mixed reaction liquid;
[0064] S4, the mixed reaction liquid was reacted at 100°C for 8h, the product was introduced into 300ml acetone, filtered to obtain a solid, dried and chromatographed using a reverse phase column with methanol / water / dichloromethane in a volume ratio of 1:1:1 as an eluent, dried to obtain a solid, washed with acetone, and then dried in vacuo at 100°C to obtain product 2 (55mg, 43% yield), the structural formula of which is shown in the following formula (8); mass spectrum data [M+Na] + :1396.43; 1H nuclear magnetic resonance spectrum: 7.79 (d, 2H, J=8.0Hz) 7.35 (m, 2H) 7.32 (m, 1H), 7.25 (s, 1H), 7.19 (m, 2H) 7.10 (m, 4H), 7.00 (d, 2H, J=8.0Hz), 6.82 (m, 6H), 5.18 (m, 6H), 4.25 (m, 1H), 3.99 (m, 12H), 3.87 (m, 5H), 3.77 (m, 6H), 3.65 (m, 6H), 3.29 (m, 6H).
[0065]
[0066] This embodiment also provides a method for preparing a perovskite solar cell, and the specific steps are similar to those of Example 1, except that Product 2 is used as the hole transport layer material, the preparation concentration of Product 2 is also 20 mg / ml, and the spin coating process is the same as that of Example 1. Finally, a perovskite solar cell using a self-passivating hole transport material is obtained.
[0067]
[0068] Comparative Example 1
[0069] This embodiment also provides a method for preparing a perovskite solar cell, and the specific steps are as follows:
[0070] S1. The FTO conductive glass substrate was ultrasonically cleaned for 15 minutes using a cleaning agent, deionized water, acetone and isopropanol in sequence, the FTO substrate was blown dry using compressed air, and then the substrate was treated with ultraviolet ozone for 15 minutes to obtain a pretreated FTO substrate.
[0071] S2, preparation of tin oxide electron transport layer, add 1g of 15% tin oxide aqueous solution to 6ml deionized water, stir at room temperature for several minutes, obtain 2.14% tin oxide colloidal aqueous solution, and spin coat the solution on the pretreated FTO substrate surface by spin coating. The spin coating process is: spread 60μl solution on the FTO surface, spin coat at 3000 rpm for 30 seconds, anneal at 150 degrees for 30 minutes, and obtain the tin oxide electron transport layer.
[0072] S3, DMF and DMSO were mixed in a volume ratio of 4:1 to obtain a mixed solvent, and methylammonium chloride MACl and Cs 0.05 (FA 0.98 MA 0.02 ) 0.95 Pb(I 0.98 Br 0.02 )3 materials are added to the mixed solvent and dissolved, Cs 0.05 (FA 0.98 MA 0.02 ) 0.95 Pb(I 0.98 Br 0.02 )3 concentration is 1.3M, MACl addition amount is 0.195M, and it is placed at 60°C for heating and stirring for 2 hours, and the perovskite precursor solution is obtained after it is completely dissolved; 40 μL of the perovskite precursor solution is added dropwise to the surface of the tin oxide electron transport layer, and the tin oxide electron transport layer is spin-coated at a speed of 4000 rpm for 30 seconds. 10 seconds before the end of the spin coating, 110 μL of anti-solvent chlorobenzene is added dropwise to the surface of the substrate to promote the rapid volatilization of the solvent, and then annealed at 120°C for 30 minutes, and cooled to room temperature to obtain a perovskite light-absorbing layer with a thickness of about 500 nm;
[0073] S4, take 60ul of 5mg / ml isopropanol solution of phenylethylamine iodide (PEAI), add it dropwise to the surface of the perovskite light-absorbing layer, and spin-coat at a speed of 5000 rpm for 30 seconds to obtain a perovskite surface passivation modification layer;
[0074] Take 72.3 mg of Spiro-OMeTAD and dissolve it in 1 ml of chlorobenzene solution. Add 31 μl of tetra-tert-butylpyridine (TBP), 19 μl of 520 mg / ml acetonitrile solution of lithium bis(trifluoromethanesulfonyl)imide and 14 μl of 380 mg / ml acetonitrile solution of cobalt bis(trifluoromethanesulfonyl)imide respectively. After fully dissolved, take 40 μl of Spiro-OMeTAD solution and add it dropwise to the surface of the above perovskite layer. Spin coat it at 3000 rpm for 30 seconds to obtain a Spiro-OMeTAD hole transport layer.
[0075] S5, the surface of the conductive substrate prepared in the above step is covered with a mask plate, and then placed in a thermal evaporation chamber, and evacuated to 10-4 Pa below A Ag film with a thickness of 100 nm is deposited at a deposition rate as a metal counter electrode layer, thereby obtaining a perovskite solar cell using a self-passivating hole transport material.
[0076] The performance tests of the perovskite solar cells assembled in Examples 1, 2 and Comparative Example 1 were respectively carried out. The open circuit voltage of the perovskite solar cell prepared in Example 1 was 1.122 V, and the short circuit current density was 24.40 mA / cm 2 , the fill factor is 80.98%; the open circuit voltage of the perovskite solar cell prepared in test example 2 is 1.111V, and the short circuit current density is 24.37mA / cm 2 , the fill factor is 80.58%; the open circuit voltage of the perovskite solar cell prepared in comparative example 1 is 1.092V, and the short circuit current density is 24.26mA / cm 2 , the fill factor is 78.65%, and the IV curves of the three devices are as follows Figure 3 As shown. From the performance test of the perovskite solar cells assembled in Examples 1 and 2 and Comparative Example 1, it can be seen that the open circuit voltage and fill factor of the battery device are significantly improved by using the hole transport material designed and synthesized by the present invention, which effectively inhibits the interface recombination between the perovskite layer and the hole transport layer and promotes the transmission of interface carriers.
[0077] Those skilled in the art should understand that the above are only some specific embodiments of the present invention, rather than all embodiments. It should be noted that for those of ordinary skill in the art, many modifications and improvements can be made, and all modifications or improvements that do not exceed the scope of protection of the present invention should be regarded as the scope of protection of the present invention.
Claims
1. A self-passivating hole transport material, characterized in that: It has the following structural formula (1): Wherein, n in formula (1) represents the number of pyranose glucose units or pyranose glucose-like units, which is any integer from 5 to 20, and the pyranose glucose units or pyranose glucose-like units form a macrocyclic structure connected end to end; the organic groups R1, R2, and R3 are the same or different, and are independently selected from one of hydrogen, halogen, alkane, alkene, alkynyl, aromatic, thienyl, pyrrolyl, and pyridyl.
2. The self-passivating hole transport material according to claim 1, characterized in that The R1, R2, and R3 can also be independently selected from at least one substituent having the formula (2): In formula (2), R4 and R5 can be independently selected from a benzene ring, a thiophene ring, a pyrrole ring, or a pyridine ring; R6 is a triphenylamine substituent, a C1-C6 alkyl substituted triphenylamine, a C1-C6 alkoxy substituted triphenylamine, a diphenylamine, a C1-C6 alkyl substituted anilino, or a C1-C6 alkoxy substituted diphenylamine; R1, R2, R3, R4, R5, and R6 groups are the same or different; m represents the number of substituents R4, which is any integer from 1 to 6.
3. The self-passivating hole transport material according to claim 1, characterized in that: The pyranose glucose units or pyranose-like units form a macrocyclic structure connected end to end and have the general characteristics of formula (3): Wherein k represents the number of pyranose glucose units or pyranose glucose-like units in the macrocyclic structure of the general formula required by formula (3), and the value is any integer between 0 and 15.
4. A method for preparing a self-passivating hole transport material according to any one of claims 1 to 3, characterized in that: The steps include: S1. A compound having a macrocyclic structure composed of pyranose glucose units or quasi-pyranose glucose units is used as a raw material, 1-toluenesulfonyl-1H-imidazole or p-toluenesulfonyl chloride is used as a reactant, and the raw material and the reactant are added to an acidic or alkaline solvent in a molar ratio of 1:(1-50) to obtain a mixed solution; S2, reacting the mixed solution under inert gas protection, first in an ice bath and then in heating or directly in heating, washing with acid, distilling and filtering to obtain a solid, subjecting the solid to reverse phase column chromatography, eluting with a mixed solvent, concentrating and drying to obtain an intermediate; S3, mixing the intermediate and a substituent containing three substituents of R1, R2 and R3 in a molar ratio of 1:(1-50), and adding the mixture into a solvent to obtain a mixed reaction liquid; the substituent containing three substituents of R1, R2 and R3 is a trifluoromethylsulfonic acid substituent containing three substituents of R1, R2 and R3, or a yellow acyl chloride substituent containing three substituents of R1, R2 and R3, or an amino substituent containing three substituents of R1, R2 and R3; S4. The mixed reaction liquid is reacted at a temperature of 50-180°C for 6h-72h, the product is added to acetone, filtered to obtain a solid, the solid is dried and then subjected to reverse phase column chromatography, eluted with a mixed solvent, and dried to obtain a solid, the solid is washed with acetone and then vacuum dried to obtain a self-passivating hole transport material.
5. The method for preparing a self-passivating hole transport material according to claim 4, characterized in that: The compound containing a macrocyclic structure composed of pyranose glucose units or pyranose glucose-like units is an organic molecule having the general structure of formula (4), wherein h in formula (4) is any integer between 0 and 15; 6. The method for preparing a self-passivating hole transport material according to claim 4, characterized in that: The acidic or alkaline solvent in step S1 is a pyridine solvent, or a mixed solvent of dioxane, water and carbonate buffer solution in a volume ratio of 1:1:
1.
7. The method for preparing a self-passivating hole transport material according to claim 4, characterized in that: The mixed solvent described in step S2 and step S4 is a methanol / water mixed solvent with a volume ratio of 1:1, or a methanol / water / dichloromethane mixed solvent with a volume ratio of 1:1:
1.
8. The method for preparing a self-passivating hole transport material according to claim 4, characterized in that: The mixed reaction liquid of step S3 is further added with a phase transfer catalyst, wherein the phase transfer catalyst is one or a combination of two or more of crown ether, alkyl-substituted amino hexafluorophosphate, alkyl-substituted ammonium bromide, 18-crown-6, and potassium carbonate.
9. The method for preparing a self-passivating hole transport material according to claim 4, characterized in that: In step S2, the reaction time under ice bath conditions is 2 to 18 hours; the reaction temperature under heating conditions is 50° C. to 180° C. and the reaction time is 2 to 8 hours.
10. Use of the self-passivating hole transport material according to any one of claims 1 to 3 in a photoelectric device, characterized in that: The photoelectric device is a perovskite solar cell, comprising a transparent conductive substrate, an electron transport layer, a perovskite layer, a hole transport layer and a metal electrode, wherein the material of the hole transport layer is the self-passivating hole transport material according to any one of claims 1 to 3.